Relationship between the dielectric and mechanical properties and the ratio of epoxy resin to hardener of the hybrid thermosetting polymers - Dias Filho, Newton Luiz [UNESP]; De Aquino, Hermes Adolfo [UNESP]; Pires, Geovanna [UNESP]; Caetano, Laércio [UNESP] (FapUNIFESP (SciELO), 2006)
The relationship between the dielectric properties (dielectric constant, ε′, and loss factor, ε; activation energy, E a) and the ratio of epoxy resin (OG) to hardener of the epoxy resin thermosetting polymers was investigated. The amplitude of the ε″ peak decreases with increasing OG content until about 73 wt.% and slightly increases at higher OG content. The temperature of the position of the ε″ peak increases with the increasing of OG content, reaching maximum values for compositions in the range of 67 and 73 wt.%, and then it decreases sharply at higher OG content. The activation energy obtained from dielectric relaxation increased with increasing wt.% OG up to around 70 wt.%. Further increase in concentration of OG up to 83 wt.% reduced E a. The curves of tensile modulus and fracture toughness mechanical properties as a function of OG content presented a similar behavior. ©2006 Sociedade Brasileira de Química.
Keywords: Dielectric analysis; Dieletric relaxation; Epoxy resin; Thermosetting materials